Idiopathic dilated cardiomyopathy as cor bovinum in infancy: “A foggy road in winter” - Das, Debasish; Banerjee, Anindya; Das, Tutan; Singh, Shashikant; Gupta, Jaideep Das; Pramanik, Subhas (Indian Journal of Child Health, 2021)
Dilated cardiomyopathy, when diagnosed in infancy, poses an array of difficulties from reaching an etiological diagnosis to prognosticating the long-term outcome. Here, we report a case of idiopathic dilated cardiomyopathy in a 6-month-old child who responded well to beta-blocker (Carvedilol) in optimum dosage and revealed favorable cardiac remodeling over 6 months with substantial improvement in ejection fraction (EF) (EF of 22–44%) with significant amelioration of child’s symptoms. Our case has a unique message that while treating idiopathic dilated cardiomyopathy (DCM) in infancy, optimized use of the beta-blockers is most often the only way to clear the foggy road of idiopathic DCM and obtain a favorable outcome.